Two-dimensional heterospectral correlation analysis of the redox-induced conformational transition in cytochrome c using surface-enhanced Raman and infrared absorption spectroscopies on a two-layer gold surface - Zou, Changji (2013)
The heme protein cytochrome c adsorbed to a two-layer gold surface modified with a self-assembled monolayer of 2-mercaptoethanol was analyzed using a two-dimensional (2D) heterospectral correlation analysis that combined surface-enhanced infrared absorption spectroscopy (SEIRAS) and surface-enhanced Raman spectroscopy (SERS). Stepwise increasing electric potentials were applied to alter the redox state of the protein and to induce conformational changes within the protein backbone. We demonstrate herein that 2D heterospectral correlation analysis is a particularly suitable and useful technique for the study of heme-containing proteins as the two spectroscopies address different portions of the protein. Thus, by correlating SERS and SEIRAS data in a 2D plot, we can obtain a deeper understanding of the conformational changes occurring at the redox center and in the supporting protein backbone during the electron transfer process. The correlation analyses are complemented by molecular dynamics calculations to explore the intramolecular interactions.